Implementation of the EPICS2017 database for photons in Geant4 - Li, Zhuxin; Michelet, Claire; Incerti, Sébastien; Ivanchenko, Vladimir; Novak, Mihaly; Guatelli, Susanna; Seznec, Hervé (Physica medica)
This paper describes in detail the implementation of Geant4 Livermore electromagnetic physics models based on the EPICS2017 database for the low energy transport of photons. These models describe four photon processes: gamma conversion, Compton scattering, photoelectric effect and Rayleigh scattering. New parameterizations based on EPICS2017 were performed for scattering functions of Compton effect, subshell cross-sections of the photoelectric effect and form factors of Rayleigh scattering, in order to improve the precision of fitted values compared to tabulated values. Comparisons between new and old parameterizations were also carried out to evaluate the precision of the new parameterizations. The models were tested through a comparative study, in which the mass attenuation coefficient was calculated for both total photon interaction and each process using Geant4 simulations based on EPICS2017 and EPDL97 respectively. The results obtained from the simulations were found in good agreement with the XCOM reference data.